Radiotherapy and long-term sequelae in pediatric patients with parameningeal rhabdomyosarcoma: results of two Cooperative Weichteilsarkom Studiengruppe (CWS) trials and one registry - Sparber-Sauer, Monika; Dietzschold, Maximilian; Schönstein, Anton; Heinz, Amadeus; Vokuhl, Christian; Pajtler, Kristian Wilfried; Harrabi, Semi B.; Lin, Yi-Lan; Kalle, Thekla von; Hagen, Rudolf; Ladenstein, Ruth; Kazanowska, Bernarda; et al. (Pediatric blood & cancer, 2024)
Background Parameningeal location of rhabdomyosarcoma (PM RMS) is known to be an unfavorable prognostic factor. Scarce data are available on radiotherapy (RT) concepts with regard to outcome. Methods Treatment and outcome of 395 children with PM RMS registered within two Cooperative Weichteilsarkom Studiengruppe (CWS) trials and one registry (1995-2021) were evaluated. Results Patients were IRS group II (n = 15) and III (n = 380) and received systemic treatment according to the enrolled protocols: I2VA (n = 172), VAIA/CEVAIE (n = 223). Delayed resection was performed in 88/395 (22%) patients, and RT was additionally given in 79/88 (90%) resected patients. RT was the predominant local treatment in 355/395 (90%) patients: hyperfractionated accelerated photon (HART; n = 77), conventionally fractionated photon (n = 91) or proton beam (n = 126), brachytherapy (n = 4), heavy ions (n = 1), not available (n = 56). In the subgroup of RT as only local treatment (n = 278), no intracranial tumor extension and complete remission at end of treatment were significant positive prognostic factors. No significant difference on tumor outcome was seen between different radiotherapy concepts. Long-term toxicity with mostly endocrinological and visual deficiencies was reported in 161/279 (58%) surviving patients with a lower trend after proton beam RT (48%) when compared to HART or conventionally fractionated photon RT (71% and 72%, respectively). Ten-year event-free and overall survival in the overall group were 62% (±5, 95% confidence interval [CI]) and 67% (±5, 95% CI); in the RT-only group 67% (±6, 95% CI) and 71% (±6, 95% CI), respectively. Conclusion CWS data confirm the recent RT concept in PM RMS. Long-term sequelae as endocrinological and visual deficiencies need to be addressed.
Zuerst veröffentlicht: 25. Oktober 2023
Gesehen am 29.01.2024